Description of the final larval stadium of Miocora aurea (Ris, 1918) (Odonata: Polythoridae) - Novelo-Gutiérrez, Rodolfo; Bota-Sierra, Cornelio Andrés (Zootaxa, 2022)
The larva of Miocora aurea (Ris, 1918) was found in first and second order forested streams at the Tatamá National Park in the Colombian Western Andes. Here it is described and figured the final larval stadium. It differs from the larva of M. chirripa (Calvert, 1917) by a combination of features such as antennal pedicel (0.25x longer than 3rd antennomere), prementum (0.20x longer than its widest part), and posterior margin of tergite 10 with a moderate incision.